Plasticity of rhizosphere hydraulic properties as a key for efficient utilization of scarce resources - Carminati, Andrea; Vetterlein, Doris (Annals of botany, 2013)
BackgroundIt is known that the soil near roots, the so-called rhizosphere, has physical and chemical properties different from those of the bulk soil. Rhizosphere properties are the result of several processes: root and soil shrinking/swelling during drying/wetting cycles, soil compaction by root growth, mucilage exuded by root caps, interaction of mucilage with soil particles, mucilage shrinking/swelling and mucilage biodegradation. These processes may lead to variable rhizosphere properties, i.e. the presence of air-filled gaps between soil and roots; water repellence in the rhizosphere caused by drying of mucilage around the soil particles; or water accumulation in the rhizosphere due to the high water-holding capacity of mucilage. The resulting properties are not constant in time but they change as a function of soil condition, root growth rate and mucilage age.ScopeWe consider such a variability as an expression of rhizosphere plasticity, which may be a strategy for plants to control which part of the root system will have a facilitated access to water and which roots will be disconnected from the soil, for instance by air-filled gaps or by rhizosphere hydrophobicity. To describe such a dualism, we suggest classifying rhizosphere into two categories: class A refers to a rhizosphere covered with hydrated mucilage that optimally connects roots to soil and facilitates water uptake from dry soils. Class B refers to the case of air-filled gaps and/or hydrophobic rhizosphere, which isolate roots from the soil and may limit water uptake from the soil as well water loss to the soil. The main function of roots covered by class B will be long-distance transport of water.OutlookThis concept has implications for soil and plant water relations at the plant scale. Root water uptake in dry conditions is expected to shift to regions covered with rhizosphere class A. On the other hand, hydraulic lift may be limited in regions covered with rhizosphere class B. New experimental methods need to be developed and applied to different plant species and soil types, in order to understand whether such dualism in rhizosphere properties is an important mechanism for efficient utilization of scarce resources and drought tolerance.